The Effect of Green Bean Sprout Peels Flour on Physical Carcasses Composition of Male Bali Duck Aged of 8 Weeks - R. P., Putra; Suasta, I M.; Sukmawati, N. M. S. (Jurnal Peternakan Tropika, 2019)
The study aimed to determine the effect of green bean sprout peels flour on the physical carcass composition of male bali duck age of 8 weeks has been carried out at the Sesetan Farm Faculty of Animal Husbandry, Udayana University, located at Jalan Raya Sesetan, for 8 weeks. The experimental design used a Completely Randomize Design (CRD) consisting of three treatments, namely: ducks fed ration without green bean sprout peels flour (P0), ducks fed ration contain 6% green bean sprout peels flour (P1), ducks fed ration contain 12% green bean sprout peels flour (P2). Each treatment consisted of five replications and each replication used three male bali ducks aged of 3 days with an average body weight of 42.90 g ± 1.98 g. The variables observed were slaughter weight, carcass weight, carcass percentage, meat percentage, bone percentage, and percentage of subcutaneous fat including skin. The results showed that ducks fed ration contain 6% green bean sprout peels flour (P1) and ducks fed ration contain 12% green bean sprouts peels flour (P2) were statistically not significantly different (P> 0.05) with treatment without green been sprout peels flour (P0) on slaughter weight, carcass weight, carcass percentage, and physical carcass composition of male male bali ducks aged of 8 weeks.. Based on the results of this study it can be concluded that the giving of 6% to 12% green bean sprout peels flour gives the same results with control, covering : slaughter weight, carcass weight, carcass percentage, and physical carcass composition of male male bali ducks aged of 8 weeks.   Keywords: Green bean sprout peels flour, male bali duck, physical carcass          composition.